A Hero’s Journey in Ernest Cline’s Ready Player One - Bryan Pandu Prakoso Wicaksono (Tell : Teaching of English Language and Literature Journal, 2020)
This research emphasizes the use of the monomyth concept in Ernest Cline's Ready Player One novel. The researcher chooses the related novel because of the heroic theme that embodied within the novel. The purpose of this research is to analyze the heroic adventure of Wade Watts in Cline's novel. To analyze the concept of the hero's journey in Cline's Ready Player One, the researcher uses the monomyth concept based on Campbell's 'Hero with the Thousand Faces Commemorative Edition' (2004). There were several studies related to the hero's journey; most of many researchers use monomyth theory by Christopher Vogler. Meanwhile, in this article, the researcher uses Joseph Campbell's monomyth concept, which has seventeen monomythic stages with more detailed and elaborate on the explanation compared to Vogler. Therefore the step of the heroic journey can be well delivered to the reader. Working on this research, the researcher uses a descriptive approach to the qualitative method. Based on the final result of the research, the researcher concludes that the main character indeed depicted as a hero, and the monomyth concept is also applied in "Ready Player One" novel.